Gut microbe‐modulated metabolites are longitudinally associated with higher neurodegeneration biomarkers in cerebrospinal fluid (CSF). (20th December 2022) - Heston, Margo B.; Carlsson, Cynthia M.; Engelman, Corinne D.; Jonaitis, Erin M.; Van Hulle, Carol A.; Deming, Yuetiva; Johnson, Sterling C.; Asthana, Sanjay; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Wild, Norbert; Blennow, Kaj; et al.
Abstract: Background: Gut bacterial metabolites in circulation and postmortem brain tissue differ in abundance between cognitively unimpaired (CU) and Alzheimer's disease (AD) individuals. Furthermore, in mice chronic injection of bacterial components exacerbates AD pathology. In CSF, we found the microbially‐produced trimethylamine‐N‐oxide was linked to AD and neurodegeneration biomarkers. However, the broader extent to which microbe‐modulated metabolites relate to AD and neurodegeneration is unknown. We tested the hypothesis that in CSF of non‐demented adults, elevated metabolites would longitudinally associate with higher biomarkers. Method: CSF was collected biannually in the Wisconsin Alzheimer's Disease Research Center and Wisconsin Registry for Alzheimer's Prevention studies. Biomarkers of pTau181, Aβ42, tTau, axonal (NfL) and synaptic (neurogranin, α‐synuclein) degeneration were quantified using Elecsys assays (NeuroToolKit robust prototype, Roche Diagnostics). Metabolite relative abundances were quantified via untargeted metabolomics analysis (ultrahigh performance liquid chromatography‐tandem mass spectrometry, Metabolon). A priori literature and database review identified 76 detected microbe‐modulated metabolites. 200 CU participants with two or more analyzed CSF samples were included in statistical analysis (Table 1). For each metabolite‐biomarker pair, multilevel linear growth modeling tested person‐level mean metabolite effects on biomarker slope and intercept, and time‐varying metabolite effects on biomarker intercept (Figure 1). Covariates included age, sex, and APOE risk score; Benjamini‐Hochberg corrections adjusted for Type I error inflation. Result: Seven metabolites were positively associated with biomarker slope or intercept (Table 2). Mean gluconate, glycerate, and oxalate levels were correlated with increased tTau slope, and N‐acetylaspartate, N‐acetylglutamate and cholesterol were correlated with higher a‐synuclein or neurogranin intercepts. Phenol sulfate was linked to tTau and α‐synuclein trajectories. To our knowledge, this is the first study detecting phenol sulfate in human CSF. No metabolites significantly associated with NfL or pTau181 /Aβ42 . Conclusion: In CSF, participants with higher mean levels of bacteria‐utilized metabolites exhibited accelerated neurodegeneration (tTau). Gluconate is metabolized by Bifidobacterium and Lactobacillus, two genera reduced in AD. Furthermore, the microbially‐produced phenol sulfate predicted greater tTau development and synaptic degeneration. Uremic toxins related to phenol sulfate dysregulate endothelial barriers in the central nervous system and vascular tissues. Additional studies should evaluate microbial metabolites as mediators of gut microbiome‐neurodegeneration relationships, and should determine if they represent modifiable pathways.